First-Principles Study of Adsorption of Methane on Defective Silicene - Adhikari, T.; Pantha, N.; Adhikari, N. (Journal of Nepal Physical Society, 2022)
Considering the significance of natural gas, such as methane, and the difficulties in storing it, research is increasingly focusing on developing materials for solid-state methane storage. Two-dimensional materials have a large number of possible adsorption sites for gas molecules due to their high surface-to-volume ratio. However, the two-dimensional structure is chemically inactive and attracts nonpolar gases rather weakly. We investigated the methane gas adsorption capabilities of silicene by activating it with different defects. According to our density functional theory calculations, the mono-vacancy (MV) defect is advantageous in increasing the binding strength of energy-carrying gases such as methane. In MV defective silicene, methane adsorption energy is detected in the order of the internationally specified energy regime.